Detection of AAD at the level of T12 vertebrae by using three Dimensional (MDCT) Angiography in subset of Karachi Population - Rosheena Nabeel Khan, Maria Mohiuddin, Mubina Lakhani, Madeeha Sadiq, Nuzhat Hassan, Abdul Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diameter of abdominal aorta at T12 vertebral level by the use of Multidetector Computer Tomography Angiography (MDCTA). Study Design: It is a Cross-sectional study. Place and Duration of Study: This study was executed in Ziauddin University (Hospital) Clifton campus Karachi, at Radiology Department, from March 2017 to August 2017. Materials and Methods: Total 160 individuals were enrolled, 75 (46.9%) were females and 85 (53.1%) were males who do not have any abdominal and arterial or venous problems, approach to Radiology Department, for Abdominal 3D Computed Tomography Angiography. Patients who were enrolled in current study were referred to department of Radiology for different indications like adrenal and renal pathologies altered bowel habits and abdominal aches. In current study abdominal aortic dimension (diameter) was analyzed at T12 vertebral levels in both sexes. The SPSS version used in current study was 20 for statistical analysis. Pearson correlation was applied to check the relationship between variables, Independent sample T test was applied. P-value is less than or equal to 0.05 was considered significant. Result: The results of current study revealed that the mean diameter of the abdominal aorta, measured at T12 vertebral level was 20.402±2.54 mm in total 160 individuals. It was observed that male having diameter with 21.47±2.25 and female have 19.18±2.31mm. It clearly showed that male having greater diameter with highly significant values P=0.001. it was also found that there was a high positive correlation was evident in between diameter of abdominal aorta & age with highly significant difference P=0.001 and r =0.713. This correlation showed that as the age increases the thickness of abdominal aorta also increases. Conclusion: It is the first study conducted in Pakistan on detection of abdominal aortic diameter at T12 vertebral level by Multidetector computed tomography angiography. The current study showed that male having greater aortic diameter than in females it also revealed that the age have a great impact on the diameter of abdominal aorta. Keywords: